2022
DOI: 10.3314/mmj.22.003
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Stewardship Task Shifting Required of Pharmacists

Abstract: Similar to antimicrobial stewardship, the concept of antifungal stewardship (AFS) has also received attention. AFS outcomes include reduced healthcare costs, avoidance of adverse events, and increased implementation of therapeutic drug monitoring (TDM). Several processes and outcome measures have recently been reported for implementing AFS and evaluating its effectiveness in healthcare institutions. This review focuses on our AFS efforts to standardize treatment using a template for pharmacist-led patient inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Ebihara et al. reported similar challenges in human resources while implementing a template to standardise and evaluate voriconazole TDM 9 . However, it was reported that a standardised template steadily increased the number of pharmacists documenting interventions 9 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ebihara et al. reported similar challenges in human resources while implementing a template to standardise and evaluate voriconazole TDM 9 . However, it was reported that a standardised template steadily increased the number of pharmacists documenting interventions 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Ebihara et al reported similar challenges in human resources while implementing a template to standardise and evaluate voriconazole TDM. 9 However, it was reported that a standardised template steadily increased the number of pharmacists documenting interventions. 9 Another study found that developing simple auto-text tools improved the productivity of pharmacists when working with EMR systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with increasing concerns about the emergence of antifungal resistance, there is a growing consideration in many countries to incorporate Antifungal Stewardship (AFS) into existing stewardship programs. This approach aims to address issues hindering the appropriate use of antifungal drugs and optimize their utilization [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since pharmacists play many roles in AFS, including drug selection, dose and dosage, confirmation of treatment duration, and therapeutic drug monitoring, this study aims to assess the use of systemic antifungals at Hospital Clínica Biblica (HCB) and to determine whether comorbidities and risk factors in patients receiving systemic antifungals may be associated with the development of more serious fungal infections, in order to facilitate the implementation of a hospital policy that allows for the best possible use of these medications and, consequently, yields the best clinical results associated with its use [ 10 ].…”
Section: Introductionmentioning
confidence: 99%